DESIGN OF BORED PILE FOUNDATIONS AND TIE BACK WALLS OF GRAND THEATER SENEN CINEMA - Deric
The Grand Theater Senen Cinema is designed to have 3 levels of main building and 2 levels of basement as a parking lot. In this project, geotechnical expertise is needed to design a foundation system to carry the structural loads and a retaining wall system to ensure safety during the basement excavation work. There are 2 locations to be reviewed in designing foundations system, which includes the basement (foundation starting point at a depth of 8,75 m) and the main building (foundation starting point at a depth of 0 m). The foundation system used are bored piles made of reinforced concrete with a diameter of 800 mm. The bored piles will be divided into several pile group configurations with 3 variations of foundation depth points. The design of the foundation system is carried out by considering the axial bearing capacity, lateral bearing capacity using Ensoft GROUP, and settlement using PLAXIS 3D. The retaining wall system is designed as an 8,75 meter deep excavation protection system which the analysis process is carried out using PLAXIS 2D with phased construction modelling. The components that are considered in the design include value of lateral wall deformation and the value of the safety factor for the conditions of the excavation construction stage, service life, and earthquake conditions. Diaphragm walls with a thickness of 1 meter and depth of 18,5 meters will be reinforced by 1 layer of ground anchor installed at the depth of 5,5 meters. In the staging of excavations, dewatering is also carried out to lower the groundwater level from a depth of 1,8 m to 10 m. The dewatering method used is the deep well method which will be installed at 9 points.